LASER BIOPHOTONICS : Laser biophotonics. (30th June 2016) - Bashkatov, A N; Genina, E A; Priezzhev, A V; Tuchin, V V
Abstract: This issue of Quantum Electronics presents the papers that reflect the state-of-the-art of laser technologies used in biomedical studies and medical practice. Among the new technologies, one can note the methods of correlation and Doppler spectroscopy, as well as THz spectroscopy, in which biologically significant molecules are characterised by specific resonances. The latter topic is considered in the paper by Nazarov et al., where the dielectric function of aqueous solutions of glucose and albumin is studied using pulsed THz spectroscopy.